Pelatihan Tools AI bagi Siswa SMK sebagai Upaya Peningkatan Kompetensi Digital dan Kesiapan Kerja - Tri Sagirani; Darwin Yuwono Riyanto; Mochammad Arifin; Yosef Richo Adrianto; Pradita Maulidya Effendi; Martinus Sony Erstiawan (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The digital competency gap between vocational school graduates and the rapidly evolving demands of modern industry has become a pressing issue in today’s workforce. One of the main challenges lies in the limited digital literacy and insufficient practical skills of students, particularly in applying Artificial Intelligence (AI) tools to support productivity and creativity. This situation hinders the readiness of graduates to compete in an AI-driven labor market, where innovation and technological adaptability are essential. To address this challenge, a training program was designed for vocational high school students at Darma Siswa Sidoarjo with the primary objective of enhancing both their conceptual understanding and practical competencies in the utilization of AI technologies. The program adopted the Participatory Action Research (PAR) method, emphasizing collaboration and active engagement between trainers and students. It was conducted through a series of interactive workshops that combined theoretical introductions with hands-on practice. Students were guided to explore AI-based platforms such as Ideogram for visual creativity, PixVerse for multimedia production, and Suno for AI-generated music. To evaluate the effectiveness of the program, pre-test and post-test instruments were used, focusing on the dimensions of knowledge, technical skills, and student confidence in using AI tools. The findings revealed that students initially demonstrated minimal awareness and limited practical ability in AI applications, as reflected in the pre-test results. However, post-test data showed a significant improvement not only in their technical proficiency but also in their enthusiasm to further explore AI technologies. Moreover, students gained increased confidence in producing creative outputs, transforming their role from passive consumers of digital tools into active and competent content creators. In conclusion, this participatory and practice-oriented training model effectively bridges the digital competency gap, enhances students’ job readiness, and fosters an innovative mindset.